2012
DOI: 10.1111/j.1600-0706.2012.20374.x
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐specific variability in life‐cycle synchronization of an ectoparasitic fly to its avian host

Abstract: The role of environmental and host-associated factors in synchronization of host-parasite life-cycles is an important question of evolutionary ecology. Yet, only handsome of studies examined this question at the intraspecific level. Here we explore how host-associated traits, such as breeding phenology and host breeding habitat, can influence parasite phenology and co-occurrence at different spatial scales. We studied the system comprised of a generalist ectoparasitic fly Carnus hemapterus and one of its avian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 60 publications
1
19
1
Order By: Relevance
“…The prevalence and abundance of this parasite are known to depend on innate host features such as ontogeny or immune capacity (Valera et al 2004; Václav et al 2008) but also on the habitat used by its hosts (Guiguen et al 1983). Similarly to Fargallo et al (2001) and Calero-Torralbo et al (2013) we found that nest boxes were more infected than natural cavities. Microclimatic differences among nest types (see Amat-Valero et al .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence and abundance of this parasite are known to depend on innate host features such as ontogeny or immune capacity (Valera et al 2004; Václav et al 2008) but also on the habitat used by its hosts (Guiguen et al 1983). Similarly to Fargallo et al (2001) and Calero-Torralbo et al (2013) we found that nest boxes were more infected than natural cavities. Microclimatic differences among nest types (see Amat-Valero et al .…”
Section: Discussionsupporting
confidence: 89%
“…They pointed out that more information about the occurrence of Hemeromyia species was necessary before drawing any conclusions about their habitat preferences. Valera et al (2006b) also emphasised that knowledge of the natural history of these species is insufficient, what hinders addressing fundamental questions for this interesting study system (see, e.g., Soler et al 1999Soler et al , 2014Martín-Vivaldi et al 2006;Václav et al 2008;Calero-Torralbo et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Bender & Irvine 2001;Lindenmayer et al 2002Lindenmayer et al , 2009), unfavorable microclimate (Amat-Valero et al 2014;Maziarz et al 2017), and unsuitable designs for the cavity requirements of the target species (Lindenmayer et al 2016Le Roux et al 2015;Rueegger 2016, but see Goldingay et al 2015). Overall, use of natural cavities (with the smallest possible addition of artificial parts) allows lid-manipulated nest-sites to offer a better microclimate (Amat-Valero et al 2014), lower ectoparasite loads (Calero-Torralbo et al 2013), higher attractiveness for various cavity-dependent species (e.g. little owl), and low conspicuousness to predators (soil sedimentation sealed gaps around the lids that more closely resembled a natural cavity).…”
Section: Discussionmentioning
confidence: 99%
“…We do know if nest box provisioning may lead to desertion of natural cavities by rollers (Valera et al 2019). Because carnid flies are more abundant in nest boxes than in natural cavities (Calero-Torralbo et al 2013) and also more abundant in nest boxes on cliffs, nest box schemes could result in a greater exposure of rollers to this parasite, which can affect nestling body condition, immunocompetence, and survival (Hoi et al 2018 and references therein). In contrast, preferential placement (and usage) of nest boxes on trees would increase the exposure of birds to vector-borne diseases, e.g., avian malaria transmitted by blackflies and biting midges).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…However, given the dependence of the species on continued management actions, e.g., nest box schemes (Rohlf et al 2014), it has been proposed as a "conservation-reliant species" (Gameiro et al 2020). Several ectoparasites have been described for this species: carnid flies (Carnus hemapterus; Calero-Torralbo et al 2013, Václav et al 2016, biting midges, blackflies, and sandflies (Václav et al 2016, Veiga et al 2018, hematophagous mites (Václav et al 2008, Roy et al 2009, lice (Sosnowski and Chmielewski 1996), louse flies (Nartshuk andMatyukhin 2019, Veiga et al 2019a), and ticks (Hoogstraal andKaiser 1961, Tsapko 2017). Specific studies on these ectoparasites show that factors such as host body features (Clayton and Walther 2001, Valera et al 2004, Martínez-de la Puente et al 2009b, Václav and Valera 2018, breeding phenology (Martínez-de la Puente et al 2009a, Calero-Torralbo et al 2013, or habitat characteristics (Černý et al 2011(Černý et al , Manzoli et al 2013 account for variation in their abundance and prevalence.…”
Section: Introductionmentioning
confidence: 99%